SPIRITUAL PREPAREDNESS PROGRAM SEBAGAI UPAYA MITIGASI PRABENCANA PADA LANSIA DI RANTING SUMBEREJO - Ely Rahmatika Nugrahani; Yeni Suryaningsih (LPPM Universitas dr. Soebandi, 2026)
Coastal communities in Sumberejo Village, Jember Regency, are highly vulnerable to hydrometeorological and geological disasters, with older adults representing a high-risk group due to physical and psychosocial limitations. Disaster mitigation efforts have predominantly focused on technical aspects, while spiritual dimensions remain underutilized despite their potential to strengthen coping and resilience. This community service program aimed to improve pre-disaster preparedness among older adults through the implementation of a Spiritual Preparedness Program based on Self-Transcendence Theory. The program employed a participatory community-based approach involving socialization, workshops, training, and continuous mentoring conducted in collaboration with Aisyiyah Muhammadiyah Sumberejo. A total of 33 older adults participated in the activity. Evaluation results demonstrated significant improvements in participants’ preparedness indicators, with knowledge scores increasing from 50 to 90, attitudes from 40 to 80, and skills from 30 to 90 following the intervention. The program also produced community outputs, including an elderly database, spiritual needs mapping, a preparedness module, and the establishment of a community-based driving team. The findings indicate that integrating spiritual strengthening with disaster education effectively enhances psychological readiness, adaptive behavior, and community resilience among older adults. The Spiritual Preparedness Program can serve as an innovative community-based model for pre-disaster mitigation targeting vulnerable elderly populations